The Effect of Physiotherapy of Spine Deviations According to Anatomical and Kinematic Analysis - Mohammed Jasim Mohammed Al-Khalidi (Journal of Global Pharma Technology, 2017)
This research includes several axes through the use of physiotherapy by utilizing therapeutic exercises to correct the Students' curvatures of the spine as those exercises are working on the treatment of curvatures and improving the body texture for students. This study aims at recognition of training program impact that is suggested for correction of spine curvature, the study was conducted on two groups of school boys and girls by the age of (8-11) years numbered (20) students. The experimental method has been used of two equivalent partial groups that is applied therapeutic units that included therapeutic exercises for (16) weeks by a fact of (32) therapeutic units and a time of (40) minutes a unit, kinematic analysis has been used to determine the angles of curvature of the spine for students (boys and girls). The Study results signified improvement of straightness of spine for both groups; the study also recommended using of the suggested therapeutic program for individuals suffering curvatures of the spine.